Where small is beautiful - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Nguni breed of cattle, indigenous to South Africa, is being recognized as a breed that will play an important role in smallholder agriculture. Efforts to conserve it are being stepped up. In the classification of cattle, the Nguni breed is a...